2014
DOI: 10.1179/1751584x14y.0000000084
|View full text |Cite
|
Sign up to set email alerts
|

Effect of operational conditions and environment on lubricity of hydrophobins in water based lubrication systems

Abstract: In this study, the effect of operational conditions (normal load, sliding velocity) and environment (pH and ionic strength) on the lubrication properties of two different hydrophobin proteins were investigated using pin on disc tribometry and ellipsometry. The studied proteins were wild type HFBI and the glycosylated hydrophobin FpHYD5. It was observed that the friction of a stainless steel versus stainless steel contact lubricated with either of the hydrophobins did not depend on the normal load. However, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…8,12,13 However, it was observed that an increase in the amount of hydrophobins adsorbed on the surface may increase the friction and wear of sliding contacts. 8,14 Friction coefficients in hydrophobin-lubricated stainless steel contacts were in the range of 0.1-0.3, which are similar to that measured on mica surfaces lubricated with HFBI. 15 Diamond-like carbon (DLC) coatings are known for their high hardness, low friction, high wear resistance, as well as for their biocompatibility, which makes them suitable for biomedical applications.…”
Section: Introductionsupporting
confidence: 72%
See 2 more Smart Citations
“…8,12,13 However, it was observed that an increase in the amount of hydrophobins adsorbed on the surface may increase the friction and wear of sliding contacts. 8,14 Friction coefficients in hydrophobin-lubricated stainless steel contacts were in the range of 0.1-0.3, which are similar to that measured on mica surfaces lubricated with HFBI. 15 Diamond-like carbon (DLC) coatings are known for their high hardness, low friction, high wear resistance, as well as for their biocompatibility, which makes them suitable for biomedical applications.…”
Section: Introductionsupporting
confidence: 72%
“…Interestingly, in this study, friction coefficients measured in hydrophobin-lubricated experiments were at the same level (0.1-0.3) as those measured in stainless steel versus stainless steel contacts using hydrophobin additives, as previously reported. 14 We can state that in hydrophobin-containing contacts, hydrophobins played a major role in the lubrication regime. Although the friction coefficients of the original bare stainless steel and DLC coating surfaces in a water environment were quite different, these surfaces showed similar wetting properties (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phospholipids, found in rich quantities in living joints, have been found to act as a kind of effective lubricant in protecting the cartilage from damage (Oloyede et al, 2004). The formation of a hydrophobin protein layer was reported to significantly reduce friction and wear (Ahlroos et al, 2011;Hakala et al, 2014). Notable lubrication performance was also found using lactic acid solutions when silicon nitride ball was sliding silica glass .…”
Section: Introductionmentioning
confidence: 99%